2022
DOI: 10.1530/jme-21-0238
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive dysfunctions and the gut microbiota

Abstract: The gut microbiome is considered an endocrine organ that can influence distant organs and associated biological pathways. Recent advances suggest that gut microbial homeostasis is essential for reproductive health and that perturbations in the gut microbiota can lead to reproductive pathologies. This review provides an updated overview of the relationship between the gut microbiome and female reproductive diseases. Specifically, we highlight the most recent findings on the gut microbiome in gynecological patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…A recent large study by Svensson et al (2021) on stool samples reported that the abundance of 12 bacteria in the classes Bacilli, Bacteroidia, Clostridia, Coriobacteriia, and Gammaproteobacteria strongly varied between endometriosis patients (n = 66) and healthy individuals (n = 198). The discrepancy between these studies necessitates more extensive studies of how endometriosis stage, age, race, medical history, medication use, and diet affect the bacteria involved in endometriosis (Chadchan et al, 2022). An animal study reported that at 42 days after mice were intraperitoneally injected with endometrial tissue to trigger endometriosis, there was a significant elevation in the Firmicutes/Bacteroidetes ratio between the endometriotic and control mice (Yuan et al, 2018).…”
Section: Endometriosis and Endometritismentioning
confidence: 99%
“…A recent large study by Svensson et al (2021) on stool samples reported that the abundance of 12 bacteria in the classes Bacilli, Bacteroidia, Clostridia, Coriobacteriia, and Gammaproteobacteria strongly varied between endometriosis patients (n = 66) and healthy individuals (n = 198). The discrepancy between these studies necessitates more extensive studies of how endometriosis stage, age, race, medical history, medication use, and diet affect the bacteria involved in endometriosis (Chadchan et al, 2022). An animal study reported that at 42 days after mice were intraperitoneally injected with endometrial tissue to trigger endometriosis, there was a significant elevation in the Firmicutes/Bacteroidetes ratio between the endometriotic and control mice (Yuan et al, 2018).…”
Section: Endometriosis and Endometritismentioning
confidence: 99%
“…Our lab has been using archived fecal specimens to identify potential association of disruption of the fecal microbiome by oral Listeria inoculation with APOs [48, 157]. The importance of deriving as much information as possible from ongoing NHP studies is amplified by the relative difficulty and cost of such studies; thus, it is imperative that we investigate potential molecular mechanisms underlying associations between microbial niches and reproductive disease as technology advances [158]. Insight into the microbial environment of the diverse niches of the FRT could contribute to a deeper understanding of how the microbiome can impact fertility, reproductive success, and well-being of the fetus, the neonate, and the individual throughout the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no study has reported a direct link between ED and endometriosis, or between gut dysbiosis and endometriosis in humans [ 6 , 7 , 38 ]. In a recent review of the literature, the intestinal microbiota is described as an endocrine organ that can influence other organs and their signaling pathways, including the female reproductive organ [ 40 ]. Even though studies conducted on animal models suggest a link between the intestinal microbiota and endometriosis, no cause and effect relationship has been formally established between gut dysbiosis and endometriosis in humans.…”
Section: Discussionmentioning
confidence: 99%